The music of Leos Janáček : motive, rhythm, structure - Skoumal, Zdenek (Eastman studies in music., 2020)
"The first thorough theoretical study of Janáček's compositions, focusing on motivic and rhythmic structure and identifying elements that give the music coherence, character, and interest"--